2021
DOI: 10.1088/1755-1315/648/1/012136
|View full text |Cite
|
Sign up to set email alerts
|

Potential bacteria capable of remediating mercury contaminated soils

Abstract: Mercury content in ex-artisanal and small-scale gold mining areas in Cianjur District, Province of West Java, Indonesia was 7 to 36 mg L−1. It has exceeded the threshold value for industrial land. Bioremediation of mercury using mercury-resistant bacteria is attractive to remove mercury from the environment because it is more effective and less expensive. The objective of this study was to obtain potential bacteria capable of accumulating mercury to be used to remediate mercury contaminated soils in ex-gold mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the other region of Indonesia, Febria et al (2016) have isolated bacteria with the highest resistance mercury level from Sijunjung District; West Sumatra was only 250 ppm. Meanwhile, Ginting et al (2021) have reported the highest resistance mercury level up to 170 ppm around ex-gold mine tailings. The mercuryresistant fungus from contaminated agricultural soil in Buru Island had been reported to grow well at 25 ppm (Hindersah et al 2018a).…”
Section: Isolates Of Mercury Resistant Microbesmentioning
confidence: 99%
“…In the other region of Indonesia, Febria et al (2016) have isolated bacteria with the highest resistance mercury level from Sijunjung District; West Sumatra was only 250 ppm. Meanwhile, Ginting et al (2021) have reported the highest resistance mercury level up to 170 ppm around ex-gold mine tailings. The mercuryresistant fungus from contaminated agricultural soil in Buru Island had been reported to grow well at 25 ppm (Hindersah et al 2018a).…”
Section: Isolates Of Mercury Resistant Microbesmentioning
confidence: 99%
“…Researchers reported the presence of Hg-resistant bacteria from various Hg-contaminated areas. Hg-resistant bacteria from tailing contaminated with up to 3,000 mg/kg Hg in Pongkor, West Java (Irawati et al, 2012), 250 mg/kg Hg in Sijunjung District, West Sumatra (Febria et al, 2016) and 36 mg/kg Hg in soil (Ginting et al, 2021). Nonetheless, several studies verified that grampositive bacteria were predominant in Hgcontaminated tailing (Chasanah et al, 2018;Naguib et al, 2018;Niane et al, 2019), and Azotobacter bd3a was able to grow on media containing 20 mg/L of HgCl2 (Hindersah et al, 2017).…”
Section: Morphology Of Azotobacter Isolatesmentioning
confidence: 99%
“…Differences in these forms of utilizations could be analyzed and showed the different in the viable microorganisms and eventually microbial population. Many manual and commercial systems identify and characterize the microbe community with these methods [35][36][37].…”
Section: Biochemical Techniques To Determine the Microbial Diversitymentioning
confidence: 99%